Non-24-Hour Sleep–Wake Disorder and Tasimelteon: A Review for Practitioners Who Work With Blind People. (January 2022) - Yuhas, Phillip T.
Introduction: This narrative review summarizes the biology of human circadian rhythms; details the epidemiology, clinical manifestation, and diagnosis of non-24-hour sleep–wake disorder (N24SWD); and reviews the efficacy of possible treatments. Methods: Searches of targeted phrases, such as "non-24-hour sleep–wake disorder" and "tasimelteon, " were conducted on PubMed between December 2016 and March 2020. Results: As the world's population ages, health practitioners frequently work with people who are blind. Damage to the retinal ganglion cells that signal environmental irradiance levels to the suprachiasmatic nucleus prevents many of these individuals from synchronizing their internal clocks to the 24-hour day. As a result, they experience a condition called N24SWD, where the body's circadian rhythms fall in and out of phase with the solar cycle. The ability to fall asleep and remain asleep is a complex process that depends on many variables, including the release of the neurohormone melatonin. Melatonin is produced at night and is a key regulator of regular sleep cycles. Periods of interrupted sleep, increased sleep latency, and reduced total sleep time occur when melatonin production peaks during daytime. Thus, many persons with N24SWD have difficulty maintaining normal schedules due in part to the mistimed release of melatonin. Randomized clinical trials have shown that melatonin receptor agonist tasimelteon is an effective therapy for individuals with N24SWD. Other treatments have varying efficacy profiles. Conclusions: Although rare, N24SWD is a serious condition that can impair quality of life for blind persons. Tasimelteon appears to be a safe and efficacious treatment option. Implications for Practitioners: Practitioners can use this information to better understand why blind persons often report difficulties sleeping and to realize that therapeutic options are available to these individuals.